2006
DOI: 10.1002/jca.20095
|View full text |Cite
|
Sign up to set email alerts
|

Study of coagulation factor activities in apheresed thawed fresh frozen plasma at 1–6°C for five days

Abstract: The concern for the loss of activities of coagulation factors in thawed fresh frozen plasma kept at 1-6 degrees C for long periods has prevented transfusion services from using thawed plasma beyond 24 hours of storage. There is no mention of the method of collection of the plasma and/or the study of the bacterial growth in the studies reported in the literature. The present project was undertaken to investigate coagulation factor activities and bacterial growth in apheresed fresh plasma. Twenty apheresed plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 9 publications
(12 reference statements)
4
28
0
Order By: Relevance
“…We elected to use 50% type O and 50% nontype O in our group of analyzed units to more closely mimic our donor population in Canada (46% type O), whereas Sidhu et al used a 25% type O and a 75% nontype O mixture of units [20]. Sidhu et al also found no change in fibrinogen or FVII levels between Days 1 and 5 of refrigerated storage and a statistically significant loss of FV activity, mirroring our results [23]. Similarly, Neisser-Svae et al found residual FVIII activities in thawed FFP of 0.75 ± 0.13 IU/mL (mean ± SD) after 5 days of refrigerated storage [24], and von Heymann et al reported median FVIII values of 0.75 with an interquartile (25–75%) range of 0.68 to 0.88 IU/mL for thawed FFP, again showing strong similarity to our results with ACD-FFPA [25].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We elected to use 50% type O and 50% nontype O in our group of analyzed units to more closely mimic our donor population in Canada (46% type O), whereas Sidhu et al used a 25% type O and a 75% nontype O mixture of units [20]. Sidhu et al also found no change in fibrinogen or FVII levels between Days 1 and 5 of refrigerated storage and a statistically significant loss of FV activity, mirroring our results [23]. Similarly, Neisser-Svae et al found residual FVIII activities in thawed FFP of 0.75 ± 0.13 IU/mL (mean ± SD) after 5 days of refrigerated storage [24], and von Heymann et al reported median FVIII values of 0.75 with an interquartile (25–75%) range of 0.68 to 0.88 IU/mL for thawed FFP, again showing strong similarity to our results with ACD-FFPA [25].…”
Section: Discussionsupporting
confidence: 78%
“…Sidhu et al prepared a group of 20 ACD-FFPA units, comprising five units from each ABO blood group [23]. Because these investigators did not sample the units at thaw, but instead at 24, 72, and 120 hours after thaw, a comparison of recoveries between studies is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with those of previous studies [1,19]. Therefore, ELISA can be considered as a sensitive screening method for determining FVIII inhibitors in samples subjected to freezing and thawing procedures.…”
supporting
confidence: 93%
“…Sheffield et al probed the stability of Canadian thawed FP ( n = 54), produced using the buffy coat method, finding it noninferior in residual FVIII activity at 120 hours to the 0.48 ± 0.12 IU FVIII/mL reported by Sheffield et al from PRP method FP24; mean losses of 20, 14, and 41%, in FV, FVII, and FVIII, respectively were observed, with no alteration in fibrinogen activity and a 9% prolongation of PT by 120 hours [37]. Similar results were obtained in stability studies of FFPA: Sidhu et al found FV and FVIII decreases of 9 and 14% after 120 hours of refrigerated storage and no change in FII, FVII, FX, FXI, and fibrinogen ( n = 20, sodium citrate anticoagulant) [75]; and Von Heymann et al noted losses of FII, FV, FVII, FVIII, FIX, FX, and FXI ranging from −8% (FII) to −47% (FVIII) ( n = 20, acid citrate dextrose [ACD] anticoagulant) after 144 hours of refrigerated storage [76]. Cookson et al observed mean losses of 11% FV and 33% FVIII activities relative to baseline values and lesser declines of FII, FVII, FIX, and FXII after 144 hours of refrigerated storage of thawed FP made from whole blood held at room temperature for 24 hours.…”
Section: Overview: Assessing the Quality Of Transfusable Plasmamentioning
confidence: 52%